Teaching evolutionary biology: Pressures, stress, and coping - Griffith, Joyce A.; Brem, Sarah K. (Journal of research in science teaching, 2004)
Understanding what teachers need to be more comfortable and confident in their profession is crucial to the future of effective teachers and scientific literacy in public schools. This study focuses on the experiences of Arizona biology teachers in teaching evolution, using a clinical model of stress to identify sources of pressure, the resulting stresses, and coping strategies they employ to alleviate these stresses. We conducted focus groups, one‐on‐one interviews, and written surveys with 15 biology teachers from the Phoenix area. On the basis of their responses, teachers were clustered into three categories: “Conflicted,” who struggle with their own beliefs and the possible impact of their teaching, “Selective,” who carefully avoid difficult topics and situations, and “Scientists,” who see no place for controversial social issues in their science classroom. Teachers from each group felt that they could be more effective in teaching evolution if they possessed the most up‐to‐date information about evolution and genomics, a safe space in which to reflect on the possible social and personal implications with their peers, and access to richer lesson plans for teaching evolution that include not only science but personal stories regarding how the lessons arose, and what problems and opportunities they created. © 2004 Wiley Periodicals, Inc. J Res Sci Teach 41: 791–809, 2004